PERAN EKSTRAKURIKULER MARAWIS DI SMP RAUDHAH BARMAWIYAH TANGERANG - Eddiina Mardiana; Erna Lajoni; Saripatul Husna (Almarhalah, 2021)
ABSTRACTThe background of this research is that learning is essentially related to the interaction between the teacher and students. A good interaction of data is illustrated by a situation where the teacher can make students able to make students learn easily and are encouraged to learn what are the competencies determined by the school. Extracurricular is a psychomotor learning system that can help subject matter with nuances of innovation that are processed by the trainer.This research was conducted with a qualitative type. Research site at Raudhah Barmawiyah Junior High School. The subjects in this study were the principal, deputy headmaster, PAI teacher, and female students. While the data collection techniques used are observations, interviews, and documentation, data analysis techniques include data reduction, data presentation, and verification / drawing conclusions.The results of this study indicate, that Sirah Nabawiyah is religious education material that can be complemented by marawis accompaniment, extracurricular marawis supports Islamic religious education because its poetry is related to Islamic religious subject matter, Sirah Nabawiyah lessons in Islamic religious education can be easily absorbed by students with singing songs in the marawis activities, students look energetic and energetic every time they want to do exercises, this has a positive impact on students on their motor development to be ready to learn in high spirits, students who take the extracurricular are more achievers especially in educational subjects Islamic religion (PAI) is evidenced by the large number of interested students participating, the results obtained in extracurricular activities related to Islamic religious education are very satisfying, it can be seen from the significant student report cards so that they provide a sense of confidence yes.